2015
DOI: 10.1007/s10603-015-9295-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Moral Philosophies and Value Orientations in Consumer Ethics: a Post-Transitional European Country Perspective

Abstract: The purpose of this paper is to broaden knowledge of the antecedents of consumer ethics and examine them in a novel setting. Thus, two complementary pairs of variables, i.e., moral philosophies (idealism and relativism) and value orientations (individualism and collectivism), are proposed as predictors of consumer ethical beliefs. The study was conducted in a post-transitional European country where consumer ethics has not been extensively explored. Using a survey method, data were collected through an on-line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 73 publications
1
20
0
Order By: Relevance
“…While idealism makes people to follow the right actions to get desirable consequences, relativism makes people not to have universal moral codes (Forsyth, 1980). Both, idealism and relativism, have significant influence on ethical beliefs (Vitell and Paolillo, 2003) and depicts an individual's attitude toward ethics (Culiberg, 2015). Moral identity of a leader shapes his capability to take ethical decisions and has a positive relationship with ethical leadership (Nunn and Avella, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While idealism makes people to follow the right actions to get desirable consequences, relativism makes people not to have universal moral codes (Forsyth, 1980). Both, idealism and relativism, have significant influence on ethical beliefs (Vitell and Paolillo, 2003) and depicts an individual's attitude toward ethics (Culiberg, 2015). Moral identity of a leader shapes his capability to take ethical decisions and has a positive relationship with ethical leadership (Nunn and Avella, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A reliable definition of consumer ethics is ‘the moral principles and standards that guide the behavior of individuals or groups as they obtain, use and dispose of goods and services’ (Muncy & Vitell, , p. 298). Other authors have also made significant contributions to the advancement of consumer ethics from both the theoretical and empirical perspective (Al‐Khatib et al, ; Arli & Pekerti, ; Arli et al, ; Culiberg, ; Rodriguez‐Rad & Ramos‐Hidalgo, Vitell, ). A scale of consumer ethics has been developed from these studies that allows consumers’ ethical beliefs to be observed in relation to their attitude to certain behaviours that could, at best, be considered questionable.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…There is a growing body of literature that recognizes the importance of consumer ethics and the majority of these studies are approached from the vendor's perspective (Bellizzi & Hite, ; Chonko, Tanner, & Weeks, ; Singhapakdi & Vitell, ; Singhapakdi, Vitell, & Franke, ). However, there is a small but growing number of studies that analyze these ethical problems from the consumer's perspective (Arli, Leo, & Tjiptono, ; Culiberg, ; Vitell & Muncy, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumer ethical scales developed by Vitell and Muncy (2005) have been widely tested in various countries such as Australia (Chowdhury and Fernando, 2013;Pekerti and Arli, 2015;Rawwas et al, 1996); Belgium (Van Kenhove et al, 2001); China (Zhao and Xu, 2013); Egypt (Al-Khatib et al, 1995, 1997Rawwas, 2001;Rawwas et al, 1994); France (Gentina et al, 2016); Hong Kong (Chan et al, 1998;Bateman et al, 2002); Japan (Erffmeyer et al, 1999); Northern Ireland ; Lebanon (Rawwas, 2001;; Saudi Arabia, Oman and Kuwait (Al-Khatib et al, 2005); Singapore (Ang et al, 2001); Slovenia (Culiberg, 2015); Thailand (Arli et al, 2015); Taiwan (Lu et al, 2015) and most frequently in the USA (Albers-Miller, 1999;Bateman et al, 2002;Dodge et al, 1996;Flurry and Swimberghe, 2016;Gardner et al, 1999;Muncy and Vitell, 1992;Muncy and Eastman, 1998;Rallapalli et al, 1994;Rawwas and Singhapakdi, 1998;Strutton et al, 1994;Vitell and Muncy, 1992;Vitell et al, 2001). However, despite the large number of studies devoted to consumer ethics, there are still relatively few have investigated the role of religiosity in consumer ethics.…”
Section: Literature Review 21 Consumer Ethicsmentioning
confidence: 99%